2014
DOI: 10.1097/jom.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cancer Incidence in Aluminum Smelter Workers

Abstract: Bladder cancer incidence was not increased at B(a)P exposures below 40 μg/m·yr. Occupational origins for other cancers occurring above expected rates but probably unrelated to B(a)P exposure cannot be excluded. In the prebake plant, nonsignificant increases of lung cancer were observed between 2000 and 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…GC is the most common cancer worldwide and the third leading cause of global cancer-related death (1,2). As a Group Ⅰ carcinogen categorized by the IARC, BaP has been confirmed to induce several types of cancers and play important roles in gastric carcinogenesis (8,15,16,30). In this study, we aimed to explore the effects of BaP on GC cell proliferation and metastasis and its regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC is the most common cancer worldwide and the third leading cause of global cancer-related death (1,2). As a Group Ⅰ carcinogen categorized by the IARC, BaP has been confirmed to induce several types of cancers and play important roles in gastric carcinogenesis (8,15,16,30). In this study, we aimed to explore the effects of BaP on GC cell proliferation and metastasis and its regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic study found that long-term exposure to BaP significantly increased the mortality in GC patients (30), suggesting that BaP plays a critical role in GC advancement. However, little is known about BaP in GC development and progression.…”
Section: Benzo[a]pyrene Promotes Gastric Cancer Cell Proliferation Anmentioning
confidence: 99%
“…Only the studies by Gibbs et al 26 and Gustavsson et al 27 measured exposure to PAH as BaP-years determined through the monitoring of workplace air samples. However, only Gibbs et al used these measurements for reporting the risks of larynx cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Gibbs et al 26 examined the larynx cancer incidence in several cohorts of workers employed at one of five aluminium production plants in Quebec, Canada. Cumulative exposure dose and SIR were reported for the combined cohort of 16 301 men.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, authors conclude that exposure levels to know health hazards associated with the emissions from primary aluminum production should be studied to establish a clear relationship between inhaled aluminum exposure and cancer [48]. The carcinogenic mechanisms of inhaled aluminum exposure are associated to different compounds an not with the metal per se, as it is described in different studies [49].…”
Section: Metals and Its Relationship With Cancermentioning
confidence: 99%